2024
DOI: 10.1021/acsestair.4c00065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 222 nm Germicidal Ultraviolet Light on Aerosol and VOC Formation from Limonene

Olivia J. Jenks,
Zhe Peng,
Melinda K. Schueneman
et al.

Abstract: Since the 1930s, germicidal ultraviolet (GUV) irradiation has been used indoors to prevent the transmission of airborne diseases, such as tuberculosis and measles. Recently, it has received renewed attention due to the COVID-19 pandemic. While GUV radiation has been shown to be effective in inactivating airborne bacteria and viruses, few studies on the impact of GUV on indoor air quality have been published. In this work, we evaluate the effects of GUV222 (GUV at 222 nm) on the chemistry of a common indoor vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…Only one of the included studies shown in Figure was done at intermediate humidity . Humidity can impact Y SOA , sometimes increasing and sometimes decreasing it, and other times having little impact. , Future studies should explore the effect of humidity on SOA from these systems.…”
Section: Resultsmentioning
confidence: 99%
“…Only one of the included studies shown in Figure was done at intermediate humidity . Humidity can impact Y SOA , sometimes increasing and sometimes decreasing it, and other times having little impact. , Future studies should explore the effect of humidity on SOA from these systems.…”
Section: Resultsmentioning
confidence: 99%
“…22 While ozone formation chemistry has been studied extensively for broad spectrum solar light in the outdoor context, 23,24 the effects of far-UVC indoors are less well-known. Recent numerical modeling 25,26 and laboratory [26][27][28][29][30] studies show that 222 nm far-UVC can increase ozone levels [25][26][27][28][29][30] and SOA formation. 25,26,30 The laboratory studies were mostly performed in reactor systems with low or no ventilation.…”
Section: O + O2 + M→ O3 + M (R2)mentioning
confidence: 99%
“…Recent numerical modeling 25,26 and laboratory [26][27][28][29][30] studies show that 222 nm far-UVC can increase ozone levels [25][26][27][28][29][30] and SOA formation. 25,26,30 The laboratory studies were mostly performed in reactor systems with low or no ventilation. These systems differ in important ways from an indoor office environment, which is ventilated and has various reactive surfaces which act as sinks for ozone.…”
Section: O + O2 + M→ O3 + M (R2)mentioning
confidence: 99%